Anglicization of hospital information systems: Managing diversity alongside particularity. (November 2018) - Mozaffar, Hajar; Williams, Robin; Cresswell, Kathrin; Sheikh, Aziz
Highlights: Tensions exist between 'standardization' and 'localization' of HIS. The complexity of health service provision, drives calls for Anglicization of HIS. Suppliers to develop sophisticated strategies as they pursue international growth. User-supplier links need to be strengthened. Usability and productivity are central issues for HIS package procurement. Abstract: Context: Despite widespread efforts to improve the quality and safety of healthcare through use of hospital information systems (HIS), many healthcare organizations face challenges in implementation and effective use of these applications, in particular when systems have been developed internationally (mainly in the US). Suppliers of these technologies also find it challenging to produce systems that work effectively across a range of geographical, cultural and institutional boundaries. In this paper, we seek to understand the strategies used by suppliers and adopters of HIS to overcome the challenges involved in the development and adoption of generic overseas systems. Methods: We conducted a qualitative study, by interviewing 176 individuals (eight organizations), observing two user groups, and running a supplier focus group. We used inductive thematic analysis to assess emerging strategies in developing and implementing overseas packaged HIS in English settings. Findings: The health sector in England has entered a period of potentially transformative change with many international HIS suppliers entering the market. This has provoked call for the 'Anglicization' of generic systems. This endeavor, has resulted in emergence of more or less aligned supplier and user strategies to overcome the difficulties in the process. This includes a continuous process of identification and classification of requests (by suppliers), and unification and voicing of needs (by adopters). Conclusions: The complexity of health service provision, drives calls for customization of technologies in this sector. Consequent tensions between 'standardization' and 'localization' are requiring suppliers of generic solutions to develop more sophisticated strategies as they pursue international growth of their market.